An investigation of the implementation of the thematic approach in Namibian lower primary classrooms: a case study - Amukushu-Niipare, Alina (Rhodes University, Faculty of Education, Department of Education, 2008)
This study focuses on the implementation of a thematic approach in the Namibian Lower Primary Phase of schooling. The purpose of the study is to investigate teachers' perceptions and understanding of the thematic approach and also to explore how teachers plan and implement a thematic approach in their classrooms. It is argued that a thematic approach allows for a combination of subjects that integrate content across the curriculum in such a way that learners can see the relations among concepts and so build up their knowledge in a more meaningful way. The work was done in a qualitative paradigm using a case study approach. Findings reveal that the majority of teachers have a shallow conceptual understanding of the principles of a thematic approach and this causes difficulties in their practice. The investigation concludes that in order for teachers to deepen their conceptual understanding of the thematic approach, follow-up workshops are necessary to help them develop appropriate strategies for their classrooms.
Keywords: Education, Elementary -- Namibia -- Case studies; Teaching -- Namibia -- Case studies; Education -- Namibia -- Case studies; Educational change -- Namibia -- Case studies; School integration -- Namibia -- Case studies; Curriculum planning -- Namibia